Influence of food emulsifiers on cellular function and inflammation, a preliminary study - Dufrusine, Beatrice; Di Lisio, Chiara; Maurizio, Andrea; Sallese, Michele; De Laurenzi, Vincenzo; Dainese, Enrico (Frontiers in Nutrition, 2023)
Emulsifiers are extensively used as food additives and their consumption is increasing in Western countries. However, so far only few studies examined their potential effects on intestinal cellular functions and gut inflammation. The aim of this preliminary analysis was to study the emulsifiers and their concentrations capable of causing cellular damage compared to extra virgin olive oil (EVOO). We tested two commonly used emulsifiers (EMI, EMII) and EVOO on Caco-2 cells, derived from a colon carcinoma and widely used as a model of the intestinal inflammation. The diphenyltetrazolium bromide test MTT and clonogenic assay were used to study the effect of emulsifiers on cell viability. Cell migration was determined by the wound-healing assay. The inflammation was studied by measuring the levels of Interleukin 6 (IL-6), a multifunctional cytokine with a major role in the acute-phase response. Furthermore, we analysed the effect of conditioned media of Caco-2 cells treated with EMs on macrophages activation. In conclusion, our preliminary data provide evidence that EMs increase the proliferation and migration rate of Caco-2 cells. Moreover, Caco-2 cells treated with EMs enhance the IL-6 release and activated macrophages, supporting their role as proinflammatory molecules.